THE ROLE OF TOURISM IN THE WORLD, A COMPARISON OF ASIAN AND EUROPEAN TOURISM SERVICES AND AN EXAMINATION OF CERTAIN TOURISM PROBLEMS (World Bulletin of Social Sciences, 2023)
The most used types of tourism worldwide.Tourism in Europe and Asia Problems in the tourism service around the world
Keywords: Service of tourism; domestic industry; scenic spots; historical monuments